2005
DOI: 10.1038/sj.bmt.1704929
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of steroid-resistant acute graft-versus-host disease with daclizumab and etanercept

Abstract: Summary:Steroid-resistant acute GVHD (aGVHD) following allogeneic hematopoietic stem cell transplantation (alloHSCT) continues to be associated with a high mortality. We report the results of a phase II study of treatment of steroid-resistant aGVHD with the IL-2 receptor antibody daclizumab combined with the TNFreceptor fusion protein etanercept. Treatment consisted of daclizumab 1 mg/kg given i.v. on days 1, 4, 8, 15, 22 and etanercept 16 mg/m 2 s.c. on days 1, 5, 9, 13, 17. A total of 21 patients (age 15-61 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 38 publications
2
54
0
1
Order By: Relevance
“…These results confirm the higher response rate that was observed earlier in a paediatric series as compared with the series involving exclusively adult populations. 5,8,9 As far as organ involvement is concerned, all of our patients with cutaneous aGVHD responded to therapy, regardless of the grade of the disease. This result is in agreement with previous series that demonstrated the efficacy of Dac on this district.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…These results confirm the higher response rate that was observed earlier in a paediatric series as compared with the series involving exclusively adult populations. 5,8,9 As far as organ involvement is concerned, all of our patients with cutaneous aGVHD responded to therapy, regardless of the grade of the disease. This result is in agreement with previous series that demonstrated the efficacy of Dac on this district.…”
Section: Discussionmentioning
confidence: 77%
“…11,12 Dac was also found to be effective as second-line treatment of steroid-resistant GVHD in a limited number of reports that mostly referred to adult populations. [5][6][7][8][9][10] Response rates for aGVHD ranged between 29 and 68% in these series; however, data regarding the children who were included in these studies were not evaluable separately because they were not stratified by age. The only study on an exclusively paediatric population showed the safety and efficacy of Dac in treating both acute and chronic cutaneous GVHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In steroid-resistant patients, various immunosuppressive agents including antibodies against IL-2 and TNF have been attempted. [3][4][5] Outcome is very poor in patients who do not respond second-line treatment, in particular, if they have gut GVHD. Non-relapse mortality was 71% at 1-year post-HCT in patients with steroid-refractory gut GVHD.…”
mentioning
confidence: 99%
“…6 Survival rate decreases to 16% in adults not responding to steroids within 2 weeks 6 or 0% in adults and children not responding to a combination of anti-IL-2 and anti-TNF. 3,4 A second HCT from another donor could improve gut GVHD in mice. 7 We performed an HCT from a second HLA-matched sibling for treatment of severe acute gut GVHD in a patient in whom all other therapeutic approaches had been exhausted.…”
mentioning
confidence: 99%